The role of TRPV1 in chronic prostatitis: a review - Jiang, Zhipeng; Luo, Wen; Long, Zongmin; Chen, Jie (Frontiers in Pharmacology, 2024)
Chronic prostatitis is a prevalent male urinary system disorder characterized by pelvic discomfort or pain, bladder dysfunction, sexual dysfunction, and infertility. Pain and lower urinary tract symptoms (LUTS) are the most common symptoms, significantly impacting patients' quality of life and driving them to seek medical attention. Transient receptor potential vanilloid subtype 1 (TRPV1) is a non-selective calcium ion-dependent cation channel in the TRPV channel family that is widely distributed in neural tissue and plays a role in signal transmission. In this review, we provide a comprehensive overview of the current understanding of the role of TRPV1 in chronic prostatitis.The discussion focuses on the connection between TRPV1 and prostatitis pain and LUTS, and highlights the potential for targeting this channel in the development of novel treatment strategies.